2017
DOI: 10.1061/(asce)nm.2153-5477.0000114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cracking on Moisture Uptake in Strain-Hardening Cementitious Composites

Abstract: Strain hardening cementitious composites (SHCC) are a class of cement based materials which show strain hardening behaviour in tension. This is achieved by multiple microcracking, which results in a tightly spaced crack pattern with relatively small crack widths (50-80 micrometers (µm), in general) and high strain capacity (up to 4-5%). Due to their ductile behaviour and tight crack widths, SHCCs are commonly used for concrete repair applications. However, due to the tight crack width and crack spacing, moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In the case of cracked mortar, the values of the hydraulic diffusivity in the cracked domain, D ( ) cr , are known to be much higher than those measured for the sound domain [20]. Using the definition of D ( ) and C ( ) given in Equations (3) and (2), respectively one can estimate the earlier as in the work of [21]:…”
Section: Theory Of Unsaturated Water Transport In Sound and Cracked Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of cracked mortar, the values of the hydraulic diffusivity in the cracked domain, D ( ) cr , are known to be much higher than those measured for the sound domain [20]. Using the definition of D ( ) and C ( ) given in Equations (3) and (2), respectively one can estimate the earlier as in the work of [21]:…”
Section: Theory Of Unsaturated Water Transport In Sound and Cracked Cmentioning
confidence: 99%
“…In Fig. 4 (20) where m t ( ) water is the uptaken mass of water at the time t, A is the area exposed to water and water is the density of water at C 20 . In general, the simulated water absorptions agree well with the experimental ones for the studied mixtures.…”
Section: Capillary Absorption Of Water In Sound Mortarmentioning
confidence: 99%
“…In practice, however, cracks can be found in nearly all reinforced concrete structures originating, among others, from hygral or thermal shrinkage and/or mechanical loading. Nevertheless, studies concerning the impact of cracks on moisture ingress in cementitious materials have generally concluded that cracks facilitate rapid ingress of moisture as well as aggressive substances, such as chlorides, carbon dioxide, etc., [11][12][13][14][15][16][17] and subsequently may reduce the service life of reinforced concrete structures.…”
Section: Introductionmentioning
confidence: 99%
“…There are different strategies of achieving this, depending on the underlying cause of cracking. For example, if the mechanical loading is the cause, cracking can be limited by using fiber reinforcement, for example polyvinyl alcohol (PVA) fibers [ 5 , 6 ]. On the other hand, if the cracking is caused by thermal variations (such as early age temperature rise due to cement hydration or freeze-thaw damage), controlling the temperature is a good option.…”
Section: Introductionmentioning
confidence: 99%